The wonder eaudiobook - Donoghue, Emma (2016)
In this masterpiece by Emma Donoghue, bestselling author of Room , an English nurse is brought to a small Irish village to observe what appears to be a miracle — a girl said to have survived without food for month — and soon finds herself fighting to save the child's life. Tourists flock to the cabin of eleven-year-old Anna O'Donnell, who believes herself to be living off manna from heaven, and a journalist is sent to cover the sensation. Lib Wright, a veteran of Florence Nightingale's Crimean campaign, is hired to keep watch over the girl. Written with all the propulsive tension that made Room a huge bestseller, The Wonder works beautifully on many levels — a tale of two strangers who transform each other's lives, a powerful psychological thriller, and a story of love pitted against evil. Acclaim for The Wonder : "Deliciously gothic.... Dark and vivid, with complicated characters, this is a novel that lodges itself deep" ( USA Today , 3/4 stars) "Heartbreaking and transcendent"( New York Times ) "A fable as lean and discomfiting as Anna's dwindling body.... Donoghue keeps us riveted" ( Chicago Tribune ) "Donoghue poses powerful questions about faith and belief" ( Newsday )